Sexual Dysfunction among Women with Diabetes in a Primary Health Care at Semarang, Central Java Province, Indonesia - Saraswati, Lintang Dian; Udiyono, Ari; Sutrisni, Dian; Fauzi, Muh (Kesmas, 2019)
Sexual dysfunction is associated with pain during sexual intercourse. Diabetes mellitus (DM) has been reported to be one of the causal factors for sexual dysfunction in women. This cross-sectional study was conducted to describe the status of sexual dysfunction in women with DM in the Tlogosari Kulon Primary Health Care, Semarang, Indonesia, in March 2017. A total of 103 women with DM attending the health center participated in this study. Data were collected using a questionnaire-guided interview and through measurements (blood pressure and random blood glucose test). Results showed that 74.8% of women with DM had sexual dysfunction. The proportion of sexual dysfunction was higher among women in the clinical phase, with uncontrolled blood glucose levels, hypertension grade II, prolonged duration of DM of ≥ 5 years, undergoing insulin treatment, in menopause, grand multiparity, having used the tubectomy contraception method, low physical activity, depression, and consumption of antihypertensive drugs. The aging process, menopausal status, and consumption of antihypertensive drugs will increase the risk for sexual dysfunction in women with DM. It is recommended that women with DM maintain their physical activity, blood sugar levels, blood pressure, and their depression status.